Formulasi Strategi Bisnis PT Jalan Tol Perkasa - Reza Febriano; Ningky Sasanti Munir (Research Center and Case Clearing House PPM School of Management, 2021)
PT Jalan Tol Perkasa (PT JTP) is one of the strategic units of the PT. Jasa Marga (Persero), Tbk. (JSMR) which operates in the field of toll road development and maintenance. With the Covid19 pandemic, JTP needs to formulate the appropriate business strategy so that it can be implemented in order to achieve the business revenue and profit targets for the 2020-2022 period. This research is an applied research that uses a business strategy formulation framework from David David (2016). Through this framework, the quality of JTP's strategic response to potential opportunities and threats from the external environment is evaluated through the External Factors Evaluation (EFE) matrix, while JTP's strengths and weaknesses are evaluated through the Internal Factors Evaluation (IFE) matrix. The development of alternative strategies is carried out using two matrices: an internal-external matrix (IE) and a SWOT matrix (Strength, Weakness, Opportunity, Threat). From the IE matrix, it is known that JTP is in a position to hold and maintain, where the alternative business strategies that should be taken are market penetration and product development. From the SWOT matrix, three strategies can be implemented: obtaining maintenance work on all Jasa Marga Group and Non Jasa Marga toll roads, implementing Performance Based Maintenance Contracts (PBMC) with long-term contracts, and innovating maintenance products. Finally, the priority strategy that will soon be implemented is determined using the Quantitative Strategic Planning Matrix (QSPM) matrix.